Analysis of Historical Thinking Skills across Varied Students' Reading Motivations in the Text-Based Learning of History - Atqo Akmal; Aulia Rahmi Putri; Nur Afifah; Putri J.Y. Polem; Nurul Imanuwaddini (UIN Fatmawati Sukarno Bengkulu, 2025)
Historical education heavily relies on narrative texts, engaging students in the complexity of the past and societal evolution, demanding critical thinking to discern fact from interpretation. This research confronts a fundamental challenge: should historical narratives be unquestioningly accepted, or should skepticism prevail? At its core, historical thinking transcends rote memorization, demanding the critical analysis and interpretation of historical events and sources. The study seeks to bridge the gap between historical texts, students' reading motivations, and robust historical thinking skills. It delves into how students with varied motivations engage with historical texts, offering insights for pedagogical strategies. Using a true experiment within a one-shot case study design, the research investigates incorporating discourse analysis techniques into historical texts. Customized for groups based on reading motivations, the method reveals distinct patterns in historical thinking skills. The research uncovers insights into the relationship between students' reading motivations and historical thinking abilities. Notably, highly motivated students excel in recognizing historical significance and ethical dimensions. In contrast, low motivation students struggle with historical evidence evaluation. High motivation students comprehend continuity and change well, connecting past events with the present human experience. However, all groups face challenges in causal analysis and diverse historical perspectives. These findings indicate the need for targeted support across varied reading motivations to enhance historical thinking skills and foster a deeper understanding of history.